2003
DOI: 10.1289/ehp.6175
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between human semen parameters and environmental exposure to polychlorinated biphenyls and p,p'-DDE.

Abstract: Scientific and public concern exists about potential reproductive health effects of persistent chlorinated organic chemicals, such as polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethane (DDT), and dichlorodiphenyldichloroethylene (DDE, the most stable daughter compound of DDT). To explore the hypothesis that environmental exposures to PCBs and DDE are associated with altered semen parameters, we conducted a cross-sectional study of 212 male partners of subfertile couples who presented to the Mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(143 citation statements)
references
References 47 publications
6
132
2
3
Order By: Relevance
“…Details of subject recruitment have been previously described (28). Briefly, consecutive eligible men who were partners in subfertile couples being evaluated for infertility at the Massachusetts General Hospital Vincent Burnham Andrology lab between January 2000 and April 2003 were recruited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Details of subject recruitment have been previously described (28). Briefly, consecutive eligible men who were partners in subfertile couples being evaluated for infertility at the Massachusetts General Hospital Vincent Burnham Andrology lab between January 2000 and April 2003 were recruited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of PCBs, p,p′-DDE and HCB in serum was conducted by the Organic Chemistry Analytical Laboratory, Harvard School of Public Health, and has been described previously (Hauser et al 2003). Briefly, serum extracts were analyzed by gas chromatography with electron capture detection (GC/ECD) and quantified based on the response factors to an internal standard.…”
Section: Serum Pcb Pp′-dde and Hcbmentioning
confidence: 99%
“…Hauser et al 24,25 found a weak inverse association with sperm motility, but not with concentration, morphology, or altered DNA, when observing a population of 212 adults in their 30s who were partners of women considered sub-fertile in the United States. Waissmann 26 reported an association between DDT and some other solvents and decreased fertility and viable sperm concentration in semen.…”
Section: Preconceptionmentioning
confidence: 97%